Improving Students' Attitudes Toward Mathematics Through Numbered Heads Together Cooperative Learning Models with Scientific Approach - Megita Dwi Pamungkas (Indonesian Journal of Mathematics Education, 2019)
Schools in Indonesia are supposed to carry out mathematical learning well. However, in reality, mathematics learning process is, in many ways, simply delivering information without involving students to be able to build their own understanding and knowledge. Based on the observation, during the mathematics learning activities it was found that some students paid less attention, disturbed friends, did not do tasks, and did not focus on the learning processes. This study aims to improve students’ attitudes towards learning mathematics by applying the Numbered Heads Together (NHT) cooperative learning method with a scientific approach. This research was a Classroom Action Research (CAR) which was conducted collaboratively and carried out in class VIII A one of junior high school in Depok, Sleman, Yogyakarta which consists of 21 male and 15 female students. The procedure is in the form of cycles. Each cycle consists of four stages namely: planning, implementation, action, observation, and reflection. The techniques of collecting data were observation, notes, field notes, documentation, non-test instruments (attitude questionnaire), and tests. The results showed that students' attitudes toward mathematics increased. The final results of the questionnaire on students' attitudes toward mathematics showed a good category (77.78%) with an average score of 110.44. Then, for mathematics learning outcomes, students got an average score of 72.22. The number of students who were scored above 75 increased to 63.89%.